STAKEHOLDERS ROLE FOR DEVELOPING SUSTAINABLE UTILIZATION OF SUGAR PALM IN KEKAIT VILLAGE, WEST LOMBOK, WEST NUSA TENGGARA - Anggit Haryoso; Syafitri Hidayati; Setya Kurniawan; Primadika Al Manar; Edhi Sandra; Ervizal A. M. Zuhud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Indonesian sugar palm farmers progress up to date indicates less encouraging condition. In the last decade, sugar palm farmers faced thorough, complex problems from top to bottom. These complex problems could not be solved by the sugar palm farmers alone. It requires stakeholders’ role to work together to solve them. This study aims to assess which stakeholders and how their role plays in the sustainable utilization of sugar palm. The study successfully identified 15 stakeholders interested in sugar palm utilization. Sugar palm farmers had high interest in the effort to develop sustainable sugar palm utilization. The interest of sugar palm farmers in Kekait Village was generally affected by strong bond against the local culture which was still being practiced. The Department of Agriculture of West Lombok Regency had a level of influence by 16 points. The high level of influence was determined by the authority of the juridical attached to the Department of Agriculture. The authority covered coaching, mentoring, supervision and provision of assistance. The results of actors-linkage matrix analysis indicated that the level of relationship among stakeholders showed the potential for conflict, cooperation, and mutual help was low. Key words: cooperation, collaboration, Lombok Island, sustainability